DISSEMINATION OF COMMUNISM/MARXISM-LENINISM AS POLITICAL OFFENSE IN INDONESIAN: NATIONAL SECURITY PROTECTION OR ACADEMIC FREEDOM THREAT - Fernando, Zico Junius; Arifin, Firdaus; Sitepu, Sudirman (Faculty of Law, Universitas Diponegoro, 2025)
This study examines Indonesia’s historical relationship with Communism and Marxism-Leninism, ideologies linked to the Madiun Rebellion of 1948 and the 1965 attempted coup. Despite the collapse of the Soviet Union and the global decline of Communist influence, legal provisions criminalizing the dissemination of Communism under the Indonesian Penal Code remain, raising concerns about academic freedom. These laws potentially restrict scholarly discussions and research, particularly concerning the 1965 events, both in academic settings and digital platforms. Using doctrinal legal research and comparative insights from Germany and Hungary, this study concludes that criminalizing Communist dissemination is no longer appropriate in Indonesia's current socio-political context. Legal protections should instead focus on safeguarding public interest and the rights of those affected by the 1965 events. Moreover, the vague formulation of Articles 188 and 189 of the Indonesian Penal Code poses a threat to academic freedom. The research suggests that policymakers reconsider these legal provisions and develop a clearer, more precise definition of “clear and present danger” to balance national security concerns with academic freedom. This study contributes to the debate on legal reform, highlighting the need for an updated approach that allows open academic discourse while respecting the rights of those affected by historical events.